AUTOGENOUS ARTERIOVENOUS FISTULA DYSFUNCTION AND ASSOCIATED FACTORS IN PATIENTS WITH END-STAGE KIDNEY DISEASE UNDERGOING MAINTENANCE HEMODIALYSIS (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of autogenous arteriovenous fistula dysfunction and to investigate associated factors in patients with end-stage kidney disease undergoing maintenance hemodialysis.Subject and methods: An analytical cross-sectional study was conducted in 126 patients with end-stage kidney disease receiving maintenance hemodialysis via autogenous arteriovenous fistula at the Nephrology - Hemodialysis Department, Trung Vuong Hospital from June 2025 to April 2026.Results: The prevalence of autogenous arteriovenous fistula dysfunction was 22.2%. Patients with autogenous arteriovenous fistula dysfunction had longer durations of chronic kidney disease, end-stage kidney disease, and autogenous arteriovenous fistula use compared with those without dysfunction. On Doppler ultrasound, the dysfunction group had a smaller venous diameter at 10 cm from the anastomosis and higher proportions of draining vein wall thickening, anastomotic stenosis, outflow stenosis, and outflow thrombosis. Multivariable analysis identified autogenous arteriovenous fistula duration, venous flow at 10 cm, and draining vein wall thickening as independent associated factors.Conclusion: Autogenous arteriovenous fistula dysfunction was observed in 22.2% of patients undergoing maintenance hemodialysis. Clinical monitoring combined with Doppler ultrasonography may be useful for early detection of autogenous arteriovenous fistula dysfunction.
Keywords: Autogenous arteriovenous fistula (AVF), dysfunction, prevalence, associated factors, end-stage kidney disease.